RANCANG BANGUN APLIKASI PERSEDIAAN BARANG BERBASIS ANDROID PADA PT HERLINA INDAH JAKARTA - Wahyu Saputro; Mohamad Ariyanto (CKI ON SPOT, 2021)
As a form in the use of computers and the development of its systems hasbecome the most important needs in order to improve the performance of a company. Soevery process of corporate systems that run poorly can be replaced by a better system,because the provision of information more conceptual and sophisticated and can supportthe decision-making process. In-app security is necessary to protect from unwantedparties. With the security system in the application, can prevent from loss of data orgoods. The application system running PT HERLINA INDAH lacks in login, login menuand user application access data. Through observation methods and interviews withrelated parties, the suggestion of the results of this study is the need for changes inexisting inventory applications with new inventory applications. Application of inventoryof goods which is suggested by writer that is application of goods based on android. Withandroid-based applications are expected to improve performance in PT HERLINAINDAH, especially in the warehouse division.